Black rain in Hiroshima: a critique to the Life Span Study of A-bomb survivors, basis of the linear no-threshold model - Shizuyo Sutou (Genes and Environment, 2020)
Abstract Ionizing radiation is regulated by the linear no-threshold model (LNT), which asserts that the lowest doses of ionizing radiation are hazardous in proportion to the dose and dose rate. LNT is based on the data of the Life Span Study (LSS) of A-bomb survivors in Hiroshima and Nagasaki. Radiation doses of the survivors were estimated by using initial radiation (5% of blast energy) and residual radiation (10%) was neglected. The major component of residual radiation was fallout, most of which must be brought down to the ground by black rain. The rain was highly radioactive. There are three major black rain maps reporting that black rain covered wide areas of Hiroshima-City. The three lead to an important conclusion that not only A-bomb survivors but also not-in-the-city control subjects (NIC) were irradiated with residual radiation to a greater or lesser degree. This means that exposure doses in LSS were largely underestimated and that use of NIC as the negative control is faulty. Thus, LNT based on LSS is invalid. In addition, LSS ignores radiation hormesis ─ ionizing radiation is not always hazardous, but beneficial depending on doses and dose rates. Indeed, when LSS data of longevity were examined, a clear J-shaped dose-response, a hallmark of radiation hormesis, is apparent. Also, cancer mortality ratios are in the increasing order: NIC (exposed to residual radiation), A-bomb survivors (exposed to both initial and residual radiations), and the Japanese in general (no exposure). Thus, low dose radiation (LDR) is hormetic. Obstinate application of invalid LNT to regulation-unnecessary LDR has been causing tremendous human, social, and economic losses in Fukushima. Also, LNT prevents clinical application of radiation hormesis to age-associated diseases such as Alzheimer’s disease and cancers.